Violation of child socialization at school - Vavilova, О. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
Thе article reveals the features of the socialization of the child at the school through the prism of modern changes in the development of society and the rapid global transformation of social values. It analyzes the difficulties socialization in school, which inevitably leads to the necessity of considering the characteristics of  disadaptation.
Keywords: socialization; social and psychological adaptation; anxiety; study; upbringing; disadaptation; the content of education